Implementasi Pendekatan Saintifik (Scientific Approach) Dan Dampaknya Terhadap Hasil Belajar Siswa Kelas IV Di SDN Lokon Lombok Tengah - bahri31 (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2023)
The purpose of this study. First, to reveal the Implementation of the Scientific Approach. Second, to reveal the impact of the Implementation of a Scientific Approach on The Learning Outcomes of Grade IV Students. Third, to reveal the obstacles in the Implementation of the Scientific Approach in Grade IV students at SDN Lokon Lombok. The approach used in this study is a descriptive qualitative approach, the Data Collection Method in this study uses observation, interview, and documentation methods. Data analysis techniques Data analysis can be divided into two, namely: qualitative data analysis, descriptive analysis. The steps used in analyzing data are: data reducation, data presentation, verification. Data reduction, data presentation (data display), verification (verification). While checking the validity of the data is carried out using the credibility test, transferability test, depend test. The results showed that the implementation of the Scientific Approach has indeed been applied in grade IV SDN Lokon since the enactment of the 2013 curriculum. The impact of the implementation of the scientific approach on the learning outcomes of grade IV students at SDN Lokon, namely that students are increasingly active in the learning process because they are not fixated on the teacher's explanation. The obstacle to the implementation of the scientific approach (Scientific Approach) in grade IV students of SDN Lokon faced by the teacher is the large number of students in the classroom so that the classroom atmosphere becomes noisy and even there are often fights between students in the class.